2010
DOI: 10.1007/s00330-010-1950-0
|View full text |Cite
|
Sign up to set email alerts
|

Signal characteristics of focal bone marrow lesions in patients with multiple myeloma using whole body T1w-TSE, T2w-STIR and diffusion-weighted imaging with background suppression

Abstract: Objective This study analyses the diagnostic potential of Diffusion-Weighted Imaging with Background Suppression (DWIBS) in the detection of focal bone marrow lesions from multiple myeloma. The signal and contrast properties of DWIBS are evaluated in correlation with the serum concentration of M-component (MC) and compared with established T1-and T2-weighted sequences. Methods Data from 103 consecutive studies in 81 patients are analysed retrospectively. Signal intensities and apparent Diffusion Coefficients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…Our results are concordant with those of Luboldt et al [9], who found in a study of 11 patients with prostate cancer that DWI signal-to-noise ratio was higher than that for STIR (p50.007) [9]. Sommer et al [10] evaluated signal intensities in 81 myeloma patients, and found that DWI signal was higher than STIR in patients with high concentrations of M component (20 g dl -1 ), although the relationship was reversed in those patients with low concentrations of M components (,20 g dl -1 ). These results suggest that whole-body DWI technique is potentially more sensitive than conventional STIR imaging for the detection of bone disease in patients with prostate malignancy or multiple myeloma.…”
Section: Discusssionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are concordant with those of Luboldt et al [9], who found in a study of 11 patients with prostate cancer that DWI signal-to-noise ratio was higher than that for STIR (p50.007) [9]. Sommer et al [10] evaluated signal intensities in 81 myeloma patients, and found that DWI signal was higher than STIR in patients with high concentrations of M component (20 g dl -1 ), although the relationship was reversed in those patients with low concentrations of M components (,20 g dl -1 ). These results suggest that whole-body DWI technique is potentially more sensitive than conventional STIR imaging for the detection of bone disease in patients with prostate malignancy or multiple myeloma.…”
Section: Discusssionsupporting
confidence: 93%
“…spinal cord or muscle); however, as we wished to focus on the clinical challenge of lesion detection and not the biological behaviour of different tumours, we considered the lesion-to-background bone marrow ratio measurements to be sufficient. For the DWI sequence, we chose a b-value of 800, in line with others [7,10], as a compromise between obtaining lesion signal (lower values with T 2 shine-through effects) [9] and greater diffusion weighting (higher values). Other researchers have used lower b-values: Luboldt et al, b5200 [9]; Nakanishi et al, b5600 [8].…”
Section: Discusssionmentioning
confidence: 99%
“…ADC values of focal myeloma lesions have also been inversely correlated with serum paraprotein concentrations (31), and a significant positive correlation was demonstrated between ADC and bone marrow cellularity (7).…”
Section: Discussionmentioning
confidence: 96%
“…DWIBS is a promising MR sequence that may quantitatively evaluate tissue cellularity by measuring random movements of water molecules using the apparent diffusion coefficient map, which may potentially serve as a radiological biomarker of tumor-related hypercellularity (8). This characteristic has suggested the possible clinical applicability of DWIBS in intra-individual disease monitoring during follow-up of MM patients (9,10). To date, there are no published studies comparing DWIBS to T1-CE sequence in the diagnostic work-up of MM patients.…”
Section: Introductionmentioning
confidence: 99%